Perspectives on Environmental Awareness and Actions - Oracion, Enrique G. (Silliman Journal, 2023)
This paper is based on the data gathered by the author in San Vicente and by Susan Gavino who conducted the interview in the comparison municipality in Palawan. A detailed version is contained in the final report submitted to the Academy for Educational Development-Environmental Education and Communication Project (AED-GreenCom) which funded the research through a grant from USAID.